2021
DOI: 10.3389/fcimb.2021.630583
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells as an Escape Mechanism to the Immune Response in Taenia crassiceps Infection

Abstract: Murine cysticercosis by Taenia crassiceps is a model for human neurocysticercosis. Genetic and/or immune differences may underlie the higher susceptibility to infection in BALB/cAnN with respect to C57BL/6 mice. T regulatory cells (Tregs) could mediate the escape of T. crassiceps from the host immunity. This study is aimed to investigate the role of Tregs in T. crassiceps establishment in susceptible and non-susceptible mouse strains. Treg and effector cells were quantified in lymphoid organs before infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…This is associated with the exposure and intensity of infection as well as the developmental stage of the parasite and induced immune response. It may also be related to the inhibitory effect of T regulatory cells ( 8 10 ). Until now, however, it is unknown which parasitic molecules are responsible for these effects.…”
Section: Introductionmentioning
confidence: 99%
“…This is associated with the exposure and intensity of infection as well as the developmental stage of the parasite and induced immune response. It may also be related to the inhibitory effect of T regulatory cells ( 8 10 ). Until now, however, it is unknown which parasitic molecules are responsible for these effects.…”
Section: Introductionmentioning
confidence: 99%
“…Taenia crassiceps cysticercosis has been shown to drive sex hormone changes in mice and result in higher levels of sex steroids in both female and male mice [ 23 ]. As a model for human neurocysticercosis, T. crassiceps has been utilized to investigate the functions of T regulatory cells in facilitating parasitic establishment and lymphoproliferation in immunocompetent hosts [ 24 ]. Previous studies have revealed that MHC Qa-2 antigen in transgenic mice confers resistance to T. crassiceps cysticercosis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taenia solium and T. crassiceps cysticerci cause cysticercosis in humans, pigs, and mice. Their establishment and survival depend on the environment encountered in hosts [ 5 , 6 , 7 ]. It has been demonstrated that BALB/c mice are more susceptible to parasite infection than C57BL/6 mice [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the close phylogenetic relationship between Taenia crassiceps and T. solium and their antigenic and genomic similarity, the murine cysticercosis model for T. crassiceps has been widely used to study several physiological aspects of cysticercosis [ 2 , 3 , 4 ]. The resistance and susceptibility to T. crassiceps infections have been associated with the endocrine, genetic, and immune response in mice [ 5 , 6 , 7 ]. The susceptible BALB/c mouse favors a Th2 response and parasites’ growth with high levels of interleukin 4 (IL-4), IL-10 IL-13, IL-9, and transforming growth factor-beta (TGF-β), whereas the resistant C57BL/6 mouse develops a predominant Th1 response that limits the parasitic growth [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation